2009
DOI: 10.1111/j.1528-1167.2008.01896.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging abnormalities associated with vigabatrin in patients with epilepsy

Abstract: SUMMARYPurpose: Vigabatrin used to treat infantile spasms (IS) has been associated with transient magnetic resonance imaging (MRI) abnormalities. We carried out a retrospective review to better characterize the frequency of those abnormalities in IS and in children and adults treated with vigabatrin for refractory complex partial seizures (CPS). Methods: Medical records and 332 cranial MRIs from 205 infants (aged £24 months) with IS treated at 10 sites in the United States and Canada were collected. Similarly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 31 publications
2
94
1
Order By: Relevance
“…Previous studies have shown that children younger than 2 years of age were more likely to demonstrate abnormal signal intensity in the deep gray nuclei and dorsal brain stem compared with older children or adults when exposed to vigabatrin. 5,7,16 The observed abnormal signal intensity in the deep gray nuclei and dorsal brain stem in infants with relatively immature myelin exposed to vigabatrin may not be related to myelin vacuolationhence, the lack of significant alteration of D Ќ in the globi pallidi, thalami, and dorsal brain stem in our cohort of patients.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have shown that children younger than 2 years of age were more likely to demonstrate abnormal signal intensity in the deep gray nuclei and dorsal brain stem compared with older children or adults when exposed to vigabatrin. 5,7,16 The observed abnormal signal intensity in the deep gray nuclei and dorsal brain stem in infants with relatively immature myelin exposed to vigabatrin may not be related to myelin vacuolationhence, the lack of significant alteration of D Ќ in the globi pallidi, thalami, and dorsal brain stem in our cohort of patients.…”
Section: Discussionmentioning
confidence: 59%
“…Hyperintensities in basal ganglia, thalamus, brainstem and dentate nucleus have, very recently, been shown in approximately one-third of those exposed to vigabatrin [76][77][78][79]. These MRI abnormalities may occur as early as 3 months after the initiation of therapy.…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…[85] Alternatively, electrophilic metabolites can react with nucleophilic groups on proteins without covalent binding. [86] The drug-peptide + [50] Haematological abnormalities + [40] MRI abnormalities + [72][73][74] a The list is assembled by anatomophysiological systems (CNS, gastrointestinal system, skin, and renal system). This material is the copyright of the original publisher.…”
Section: Idiosyncratic Adverse Effectsmentioning
confidence: 99%
“…Symmetric magnetic resonance imaging (MRI) hyperintensities (T2 and DWI sequences) and magnetic resonance spectroscopy (MRS) abnormalities have been described in the globus pallidi, thalami, dentate nuclei and cerebral peduncles of patients with infantile spasms treated with GVG. [72][73][74] MRI abnormalities, which are supposed to depend on both high GVG dosage and younger age, are transient and disappear after GVG withdrawal. [72,73] MRS changes, in contrast, persist after GVG discontinuation; this might indicate that these changes are related to seizure activity rather than a direct drug effect.…”
Section: Cognitive Adverse Effects and Long-term Safetymentioning
confidence: 99%
See 1 more Smart Citation